1962
DOI: 10.1128/aem.10.3.193-199.1962
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of Clostridium perfringens in Foods

Abstract: A procedure is described for identifying and enumerating Clostridium perfringens in foods by means of a simplified agar plating method, followed by confirmation of black colonies in tubes of motility-nitrate medium and sporulation broth. The test is routinely completed within 48 hr. Under experimental conditions, the procedure has been used to quantitatively recover various levels of C. perfringens contamination in a variety of foods and has recovered as few as ten C. perfringens per g without interference fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0

Year Published

1964
1964
1982
1982

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(79 citation statements)
references
References 9 publications
3
76
0
Order By: Relevance
“…In addition, coliform counts were obtained using Violet Red Bile Agar with an agar overlay and clostridial counts using Sulfite-Polymyxin-Sulfadiazine Agar with an agar overlay. Isolation and quantitation of staphylococci and clostridia were performed by the methods of Baird-Parker (1962) and Angelotti et al (1962) respectively. Procedures for incubation and enumeration of all plates were the same as those given in the Bacteriological Analytical Manual (Olson, 1969), and Recommended Methods for the Microbiological Evaluation of Foods (APHA, 1966).…”
Section: Microbiological Analysissupporting
confidence: 78%
“…In addition, coliform counts were obtained using Violet Red Bile Agar with an agar overlay and clostridial counts using Sulfite-Polymyxin-Sulfadiazine Agar with an agar overlay. Isolation and quantitation of staphylococci and clostridia were performed by the methods of Baird-Parker (1962) and Angelotti et al (1962) respectively. Procedures for incubation and enumeration of all plates were the same as those given in the Bacteriological Analytical Manual (Olson, 1969), and Recommended Methods for the Microbiological Evaluation of Foods (APHA, 1966).…”
Section: Microbiological Analysissupporting
confidence: 78%
“…The slopes of the gas production curves for most strains in ground frankfurter were higher than in any of the other media. Angelotti et al (1962) reported that C. perfringens grew well in meat and meat products and Busta and Schroder (1971) indicated that the rate of growth in liquid medium, in which beef was the sole protein source, was extremely rapid. Strain S-88, which was unable to produce any significant gas in casein, whole egg or R + S media, was able to grow well in ground frankfurter medium.…”
Section: Resultsmentioning
confidence: 99%
“…For spore counts a 4 ml portion of a l/5 dilution of each blended sample was heat shocked in a water bath at 75°C for 20 min. Sulfite-polymyxin-sulfadiazine (SPS) agar, (Angelotti et al, 1962) was used for pour plates from serial dilutions. Plates were incubated anaerobically at 35°C for 48 hr.…”
Section: Methodsmentioning
confidence: 99%